Can we find solution to eliminate Li penetration through solid garnet electrolytes?. (June 2020) - Huang, W.L.; Zhao, N.; Bi, Z.J.; Shi, C.; Guo, X.X.; Fan, L.-Z.; Nan, C.-W.
Abstract: High-dense garnet electrolytes have sufficient mechanical strength and ion transference number of unity, through which blocking of Li penetration is expected. Nevertheless, the situation of Li growth through the solid garnet electrolyte is even worse than that in the case of liquid electrolyte. Many investigations have been carried out in terms of mechanism analysis and solution exploration. In this review, we classify the relevant research and point out the crucial factors that influence Li penetration across the solid electrolyte. The fundamental mechanism is summarized and the useful methods to relieve such problems are addressed. Whether or not the fundamental solution exists is answered and how to deal with such critical issue is suggested. Highlights: Critical factors influencing Li penetration and improvement strategies were reviewed. High density is priority for garnets to block Li penetration. Interface engineering is helpful to depress dendrite growth. The critical current density is determined by specific bulk materials and interfaces.